2020
DOI: 10.3389/fendo.2020.00656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Pituitary Cell Plasticity

Abstract: The mechanisms that mediate plasticity in pituitary function have long been a subject of vigorous investigation. Early studies overcame technical barriers and challenged conceptual barriers to identify multipotential and multihormonal cell populations that contribute to diverse pituitary stress responses. Decades of intensive study have challenged the standard model of dedicated, cell type-specific hormone production and have revealed the malleable cellular fates that mediate pituitary responses. Ongoing studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The presence of cells expressing more than one hormone in the anterior pituitary has been shown in many studies, both in teleosts and in mammals [for review see (27,(74)(75)(76)]. Using scRNA-seq technology, multi-hormonal cells have been described in the mouse pituitary (77), but never before in a teleost.…”
Section: Scrna-seq and Multi-color Fish Reveal The Presence Of Multi-hormonal Cells In The Adult Medaka Pituitarymentioning
confidence: 99%
“…The presence of cells expressing more than one hormone in the anterior pituitary has been shown in many studies, both in teleosts and in mammals [for review see (27,(74)(75)(76)]. Using scRNA-seq technology, multi-hormonal cells have been described in the mouse pituitary (77), but never before in a teleost.…”
Section: Scrna-seq and Multi-color Fish Reveal The Presence Of Multi-hormonal Cells In The Adult Medaka Pituitarymentioning
confidence: 99%
“…In all fish, LH and FSH are produced by different cells, whereas in most tetrapods they seem to be produced in the same cell ( Siddique et al, 2020 ). There are lines of evidence also showing that one pituitary cell type expressing multiple hormone mRNAs exists in normal rodent pituitaries ( Childs et al, 2000 ; Seuntjens et al, 2002 ; Villalobos et al, 2004 ; Childs et al, 2020 ). In chicken pituitaries, we found that lactotrophs predominantly express PRL , however, they can also weakly express LHB, GRP, GH, POMC , and TSHB .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of cells expressing more than one hormone in the anterior pituitary has been shown in many studies, both in teleosts and in mammals (for review see (28,(69)(70)(71)). Using scRNA-seq technology, multi-hormonal cells have for instance been described in the mouse pituitary (72).…”
Section: Scrna-seq and Multi-color Fish Reveal The Presence Of Multi-hormonal Cells In The Adult Medaka Pituitarymentioning
confidence: 97%